A scratch-resistant PE composite board and preparation method thereof
By using polyethylene materials such as high molecular weight polyethylene, low density polyethylene, medium density polyethylene in PE composite panels, and adding functional additives such as reinforced fillers, modified polyurethane elastomers and molybdenum disulfide, the problem of insufficient deformation and scratch resistance under external forces is solved, and the effect of improving its mechanical properties, scratch resistance and ultraviolet resistance is achieved.
Patent Information
- Application Number
- CN202411793830.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-09
AI Technical Summary
PE composite panels are prone to deformation when subjected to external forces, which affects their scratch resistance. The prior art improves hardness and wear resistance by adding fillers, but has limited effect.
High molecular weight polyethylene, low-density polyethylene, and medium-density polyethylene are used as the main raw materials, and functional additives such as reinforced fillers, modified polyurethane elastomers and molybdenum disulfide are added to prepare scratch-resistant PE composite panels through refining, hot-pressing and cold-pressing molding processes.
It improves the mechanical properties, surface hardness and scratch resistance of PE composite panels, enhances its toughness and impact resistance, and improves its ultraviolet resistance.
Smart Images

Figure GDA0005260478900000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite boards, and in particular to a scratch-resistant PE composite board and a preparation method thereof. Background Art
[0002] PE composite board is a board made of polyethylene and other materials, and the comprehensive performance of the board is improved by adding various functional additives. PE composite board is odorless, non-toxic, feels like wax, has excellent low temperature resistance, corrosion resistance, weather resistance, environmental protection and other characteristics, and can be widely used in chemical, food, medical, construction and other fields. However, the raw materials of PE composite board are relatively soft and have average tensile resistance, which makes it easy to deform when subjected to external force, thus affecting the scratch resistance of the board.
[0003] At present, the scratch resistance of PE composite board is usually improved by adding fillers such as calcium carbonate, talcum powder, barium sulfate, etc. However, the use of fillers alone may not effectively improve its hardness and wear resistance, and the improvement of scratch resistance is limited; in addition, although the composite board has a certain toughness, due to the difference in the use environment, its own toughness no longer meets the market demand. Therefore, researchers need to develop a PE composite board with excellent scratch resistance, toughness and other properties. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a scratch-resistant PE composite board and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A scratch-resistant PE composite plate comprises the following raw materials in parts by weight: 65-85 parts of polyethylene, 3-7 parts of low-density polyethylene, 2-5 parts of medium-density polyethylene, 3-8 parts of reinforcing filler, 5-12 parts of modified polyurethane elastomer, 0.5-2 parts of silane coupling agent, 2-4 parts of molybdenum disulfide, and 0.2-0.4 parts of lubricant;
[0007] Furthermore, the molecular weight of the polyethylene is between 2.8 million and 4 million, the silane coupling agent is KH-570, and the lubricant is stearic acid;
[0008] The reinforcing filler is prepared by the following steps:
[0009] Step A1, mixing and stirring the nanocellulose in ethanol, and then transferring the mixture to a planetary ball mill for ball milling at a ball-to-material ratio of 10:1 for 3-6 hours to obtain pre-treated nanocellulose;
[0010] Step A2, adding pretreated nanocellulose, 4-dimethylaminopyridine, β-alanine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and fluorenylmethoxycarbonyl chloride to N,N-dimethylformamide in sequence and mixing evenly, stirring at room temperature for 10-15 hours, centrifuging, washing, collecting the preproduct, and then dispersing the preproduct in 20% (v / v) piperidine N,N-dimethylformamide solution, stirring for 20-40 minutes, centrifuging, washing, and freeze-drying to obtain modified nanocellulose;
[0011] Step A3, mixing p-phenylenediamine and triethylamine in N,N-dimethylformamide and stirring evenly, then adding cyanuric chloride and modified nanocellulose and ultrasonicating for 20-40 minutes, then transferring to an autoclave, reacting at 120° C. for 8-12 hours, centrifuging, washing and drying to obtain a reinforced filler;
[0012] Further, in step A1, the mass ratio of nanocellulose to ethanol is 3-10:0.5-3;
[0013] Further, in step A2, the amount ratio of the pre-treated nanocellulose, 4-dimethylaminopyridine, β-alanine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, fluorenylmethoxycarbonyl chloride, N,N-dimethylformamide and piperidine N,N-dimethylformamide solution is 1-3 g: 0.08-0.24 g: 1.5-4.5 g: 1.25-3.75 g: 0.75-2.25 g: 50-100 mL: 20-40 mL;
[0014] Furthermore, in step A3, the dosage ratio of p-phenylenediamine, triethylamine, N,N-dimethylformamide, cyanuric chloride and modified nanocellulose is 5.4-16.2 g: 7-14 mL: 200 mL: 4.6-13.8 g: 1-3 g.
[0015] The modified polyurethane elastomer is prepared by the following steps:
[0016] Step B1, 2,2-dihydroxymethylpropionic acid, epichlorohydrin and tetrabutylammonium bromide are mixed uniformly in N,N-dimethylformamide, and then nitrogen is introduced for 10 minutes, and the mixture is reacted under nitrogen at 80-90° C. for 3-5 hours, and then rotary evaporated, and then 25wt% sodium hydroxide solution is slowly added dropwise, and the mixture is reacted at 60-70° C. for 2-3 hours, and then washed and dried to obtain a terminal epoxy product;
[0017] Step B2, 2-hydroxy-4-methoxybenzophenone, the terminal epoxy product and chloroform were mixed and stirred evenly, ion exchange resin (Amberlyst-15) was added, and then transferred to a water bath, reacted at 50-60° C. for 2-3 hours, filtered, and rotary evaporated to obtain a terminal hydroxyl product;
[0018] Step B3, dehydrate polyethylene glycol (molecular weight 1000) under vacuum at 130° C. for 1-2 h, introduce argon, then cool to 75-95° C., add isophorone diisocyanate and dibutyltin dilaurate to react for 2.5-4.5 h, then add toluene and the terminal hydroxyl product to stir and react for 2-3 h to obtain a modified polyurethane elastomer;
[0019] Further, in step B1, the dosage ratio of 2,2-dihydroxymethylpropionic acid, epichlorohydrin, tetrabutylammonium bromide, N,N-dimethylformamide and sodium hydroxide solution is 0.1-0.2 mol: 0.1-0.2 mol: 0.005-0.01 mol: 100 mL: 30 mL;
[0020] Further, in step B2, the usage ratio of 2-hydroxy-4-methoxybenzophenone, terminal epoxy product, chloroform and ion exchange resin is 1.14-3.42 g: 0.88-2.64 g: 5-15 mL: 0.5-1.5 g;
[0021] Furthermore, in step B3, the usage ratio of polyethylene glycol, isophorone diisocyanate, dibutyltin dilaurate, toluene and terminal hydroxyl product is 0.1 mol: 0.13-0.25 mol: 0.001-0.003 mol: 50 mL: 4-8 g.
[0022] A method for preparing a scratch-resistant PE composite board comprises the following steps:
[0023] Step S1, weighing raw materials by weight, putting polyethylene, low-density polyethylene, medium-density polyethylene, reinforcing filler, modified polyurethane elastomer, silane coupling agent, molybdenum disulfide and lubricant into an internal mixer, and mixing at 160-180° C. for 10-20 minutes to obtain a rubber mixture;
[0024] Step S2, pouring the mixed rubber into a mold and subjecting it to hot pressing and cold pressing to obtain a scratch-resistant PE composite board.
[0025] Beneficial effects of the present invention:
[0026] The PE composite plate of the invention is prepared by using high molecular weight polyethylene, low density polyethylene and medium density polyethylene as main raw materials, adding reinforcing fillers, modified polyurethane elastomers, molybdenum disulfide and other functional additives through processes such as banburying, hot pressing and cold pressing. The addition of reinforcing fillers improves the mechanical properties and surface hardness of the matrix, thereby improving the scratch resistance. The modified polyurethane elastomer is introduced into the matrix as a toughening component, which not only improves the toughness of the matrix, but also improves the scratch resistance of the matrix. The introduction of molybdenum disulfide can utilize its unique layered structure to reduce the friction coefficient of the matrix, thereby improving the scratch resistance of the matrix.
[0027] In the reinforcing filler, the nanocellulose is firstly ball-milled to obtain pre-treated nanocellulose with good dispersibility and small particle size; then, under the condition of protecting the amino group of β-alanine with fluorenylmethoxycarbonyl (Fmoc), the carboxyl group in β-alanine and the hydroxyl group in the pre-treated nanocellulose undergo esterification reaction, and then the Fmoc protecting group is removed under alkaline conditions to obtain modified nanocellulose containing amino groups on the surface; finally, p-phenylenediamine and cyanuric chloride are used as raw materials to in-situ synthesize COF (covalent organic framework) on the surface of the modified nanocellulose to obtain the reinforcing filler. The introduction of reinforcing fillers improves the scratch resistance of PE composite boards. Among them, after the nanocellulose with excellent mechanical properties is introduced into the matrix, the mechanical properties and surface hardness of the matrix are improved, which makes the matrix have a strong resistance to the compressive stress of the scraper head moving forward in the scratch test, and the resistance to scratch stress is enhanced, thereby improving the scratch resistance of the matrix. At the same time, nanocellulose can induce crystallization in the blend, which is beneficial to the improvement of crystallinity, thereby improving the scratch resistance of the matrix. In addition, COF in the reinforcing filler can work synergistically with nanocellulose, using its own high crystallinity and ordered pore structure to enable it to better disperse and transfer stress under stress, thereby improving the mechanical properties of the matrix and then improving the scratch resistance of the matrix.
[0028] In the modified polyurethane elastomer, the carboxyl group in 2,2-dimethylol propionic acid and the epoxy group in epichlorohydrin are firstly used to undergo a ring-opening reaction, and then the chloromethyl group and the hydroxyl group formed by the ring-opening are used to undergo a ring-closing reaction under alkaline conditions to obtain a terminal epoxy group product; then the epoxy group in the terminal epoxy group product is reacted with the hydroxyl group in 2-hydroxy-4-methoxybenzophenone to obtain a terminal hydroxyl group product; and then the terminal hydroxyl group product is used as a chain extender to participate in the reaction to synthesize the modified polyurethane elastomer. The modified polyurethane elastomer is introduced into the matrix as a toughening component, which can improve the toughness of the matrix. When the matrix is impacted, the modified polyurethane elastomer in the matrix becomes a stress concentration area, which can diffuse and branch the stress to the surrounding area, absorb a large amount of impact energy, and prevent the extension of cracks caused by shear stress while absorbing stress, thereby enhancing the impact resistance of the matrix and increasing the toughness of the material; in addition, the introduction of the modified polyurethane elastomer can also utilize the soft segments in its molecular structure to absorb external stress and disperse the stress on the surface of the matrix, thereby reducing damage to the surface of the matrix, enhancing the resistance to scratch stress, reducing the color difference of the matrix before and after scratching, and improving scratch resistance; in addition, benzophenone groups are also introduced into the modified polyurethane elastomer, which can improve the UV resistance of the matrix and delay aging caused by UV rays. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1: The reinforcing filler is prepared by the following steps:
[0031] Step A1, 3 g of nanocellulose was mixed and stirred evenly in 0.5 g of ethanol, and then transferred to a planetary ball mill for ball milling at a ball-to-material ratio of 10:1 for 3 h to obtain pre-treated nanocellulose;
[0032] Step A2, 1 g of pretreated nanocellulose, 0.08 g of 4-dimethylaminopyridine, 1.5 g of β-alanine, 1.25 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.75 g of fluorenylmethoxycarbonyl chloride are sequentially added to 50 mL of N, N-dimethylformamide and mixed evenly, then stirred at room temperature for 10 h, centrifuged, washed, and the pre-product was collected, and then the pre-product was dispersed in 20 mL, 20% (v / v) piperidine N, N-dimethylformamide solution, stirred for 20 min, centrifuged, washed, and freeze-dried to obtain modified nanocellulose;
[0033] Step A3, 5.4 g of p-phenylenediamine and 7 mL of triethylamine were mixed and stirred in 200 mL of N, N-dimethylformamide, and then 4.6 g of cyanuric chloride and 1 g of modified nanocellulose were added and ultrasonicated for 20 min, and then transferred to an autoclave, reacted at 120° C. for 8 h, centrifuged, washed, and dried to obtain a reinforced filler.
[0034] The modified polyurethane elastomer is prepared by the following steps:
[0035] Step B1, 0.1 mol 2,2-dimethylolpropionic acid, 0.1 mol epichlorohydrin and 0.005 mol tetrabutylammonium bromide were mixed evenly in 100 mL N, N-dimethylformamide, and then nitrogen was introduced for 10 min, and the mixture was reacted at 80° C. for 3 h under nitrogen, and then rotary evaporated, and then 30 mL of 25 wt% sodium hydroxide solution was slowly added dropwise, and the mixture was reacted at 60° C. for 2 h, washed and dried to obtain a terminal epoxy product;
[0036] Step B2, 1.14 g of 2-hydroxy-4-methoxybenzophenone, 0.88 g of the terminal epoxy product and 5 mL of chloroform were mixed and stirred evenly, 0.5 g of ion exchange resin (Amberlyst-15) was added, and then transferred to a water bath, reacted at 50° C. for 2 h, filtered, and rotary evaporated to obtain a terminal hydroxyl product;
[0037] Step B3, dehydrate 0.1 mol of polyethylene glycol (molecular weight 1000) under vacuum at 130°C for 1 h, introduce argon, then cool to 75°C, add 0.13 mol of isophorone diisocyanate and 0.001 mol of dibutyltin dilaurate and react for 2.5 h, then add 50 mL of toluene and 4 g of terminal hydroxyl product and stir to react for 2 h to obtain a modified polyurethane elastomer.
[0038] Example 2: The reinforcing filler is prepared by the following steps:
[0039] Step A1, 6 g of nanocellulose was mixed and stirred evenly in 2 g of ethanol, and then transferred to a planetary ball mill for ball milling at a ball-to-material ratio of 10:1 for 4.5 h to obtain pre-treated nanocellulose;
[0040] Step A2, 2 g of pre-treated nanocellulose, 0.16 g of 4-dimethylaminopyridine, 3 g of β-alanine, 2.5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1.5 g of fluorenylmethoxycarbonyl chloride were added to 80 mL of N, N-dimethylformamide in sequence and mixed evenly, then stirred at room temperature for 12 h, centrifuged, washed, and the pre-product was collected, and then the pre-product was dispersed in 30 mL of 20% (v / v) piperidine N, N-dimethylformamide solution, stirred for 30 min, centrifuged, washed, and freeze-dried to obtain modified nanocellulose;
[0041] Step A3: 10.8 g of p-phenylenediamine and 11 mL of triethylamine were mixed and stirred evenly in 200 mL of N, N-dimethylformamide, and then 9.2 g of cyanuric chloride and 2 g of modified nanocellulose were added and ultrasonicated for 30 min. The mixture was transferred to an autoclave and reacted at 120° C. for 10 h. The mixture was centrifuged, washed and dried to obtain a reinforced filler.
[0042] The modified polyurethane elastomer is prepared by the following steps:
[0043] Step B1, 0.15 mol 2,2-dimethylolpropionic acid, 0.15 mol epichlorohydrin and 0.0075 mol tetrabutylammonium bromide were mixed evenly in 100 mL N, N-dimethylformamide, and then nitrogen was introduced for 10 min, and the mixture was reacted under nitrogen and 85° C. for 4 h, and then rotary evaporated, and then 30 mL of 25 wt% sodium hydroxide solution was slowly added dropwise, and the mixture was reacted at 65° C. for 2.5 h, and then washed and dried to obtain a terminal epoxy product;
[0044] Step B2, 2.28 g of 2-hydroxy-4-methoxybenzophenone, 1.76 g of the terminal epoxy product and 10 mL of chloroform were mixed and stirred evenly, 1 g of ion exchange resin (Amberlyst-15) was added, and then transferred to a water bath, reacted at 55° C. for 2.5 h, filtered, and rotary evaporated to obtain a terminal hydroxyl product;
[0045] Step B3, 0.1 mol of polyethylene glycol (molecular weight 1000) was vacuum dehydrated at 130°C for 1.5 h, argon was introduced, and then the temperature was lowered to 85°C, 0.19 mol of isophorone diisocyanate and 0.002 mol of dibutyltin dilaurate were added and reacted for 3.5 h, and then 50 mL of toluene and 6 g of the terminal hydroxyl product were added and stirred for reaction for 2.5 h to obtain a modified polyurethane elastomer.
[0046] Example 3: The reinforcing filler is prepared by the following steps:
[0047] Step A1, 10 g of nanocellulose was mixed and stirred evenly in 3 g of ethanol, and then transferred to a planetary ball mill for ball milling at a ball-to-material ratio of 10:1 for 6 h to obtain pre-treated nanocellulose;
[0048] Step A2, 3 g of pre-treated nanocellulose, 0.24 g of 4-dimethylaminopyridine, 4.5 g of β-alanine, 3.75 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 2.25 g of fluorenylmethoxycarbonyl chloride were added to 100 mL of N, N-dimethylformamide in sequence and mixed evenly, then stirred at room temperature for 15 h, centrifuged, washed, and the pre-product was collected, and then the pre-product was dispersed in 40 mL of 20% (v / v) piperidine N, N-dimethylformamide solution, stirred for 40 min, centrifuged, washed, and freeze-dried to obtain modified nanocellulose;
[0049] Step A3: 16.2 g of p-phenylenediamine and 14 mL of triethylamine were mixed and stirred in 200 mL of N, N-dimethylformamide, and then 13.8 g of cyanuric chloride and 3 g of modified nanocellulose were added and ultrasonicated for 40 min. The mixture was transferred to an autoclave and reacted at 120 ° C for 12 h. The mixture was centrifuged, washed and dried to obtain a reinforced filler.
[0050] The modified polyurethane elastomer is prepared by the following steps:
[0051] Step B1, 0.2 mol 2,2-dimethylolpropionic acid, 0.2 mol epichlorohydrin and 0.01 mol tetrabutylammonium bromide were mixed evenly in 100 mL N,N-dimethylformamide, and then nitrogen was introduced for 10 min, and the mixture was reacted under nitrogen and 90° C. for 5 h, and then rotary evaporated, and then 30 mL of 25 wt% sodium hydroxide solution was slowly added dropwise, and the mixture was reacted at 70° C. for 3 h, and then washed and dried to obtain a terminal epoxy product;
[0052] Step B2, 3.42 g of 2-hydroxy-4-methoxybenzophenone, 2.64 g of the terminal epoxy product and 15 mL of chloroform were mixed and stirred evenly, 1.5 g of ion exchange resin (Amberlyst-15) was added, and then transferred to a water bath, reacted at 60° C. for 3 h, filtered, and rotary evaporated to obtain a terminal hydroxyl product;
[0053] Step B3, dehydrate 0.1 mol of polyethylene glycol (molecular weight 1000) under vacuum at 130°C for 2 h, introduce argon, then cool to 95°C, add 0.25 mol of isophorone diisocyanate and 0.003 mol of dibutyltin dilaurate and react for 4.5 h, then add 50 mL of toluene and 8 g of the terminal hydroxyl product and stir to react for 3 h to obtain a modified polyurethane elastomer.
[0054] Example 4: A method for preparing a scratch-resistant PE composite board comprises the following steps:
[0055] 65 parts of polyethylene (molecular weight 2.8 million), 3 parts of low-density polyethylene, 2 parts of medium-density polyethylene, 3 parts of reinforcing filler prepared in Example 1, 5 parts of modified polyurethane elastomer prepared in Example 1, 0.5 parts of KH-570, 2 parts of molybdenum disulfide, and 0.2 parts of lubricant;
[0056] Step S1, weighing raw materials by weight, putting polyethylene, low-density polyethylene, medium-density polyethylene, the reinforcing filler prepared in Example 1, the modified polyurethane elastomer prepared in Example 1, KH-570, molybdenum disulfide and stearic acid into an internal mixer, and mixing at 160° C. for 10 minutes to obtain a rubber mixture;
[0057] Step S2, pouring the mixed rubber into a mold and subjecting it to hot pressing and cold pressing to obtain a scratch-resistant PE composite board.
[0058] Example 5: A method for preparing a scratch-resistant PE composite board comprises the following steps:
[0059] 75 parts of polyethylene (molecular weight 3.5 million), 5 parts of low-density polyethylene, 3 parts of medium-density polyethylene, 5 parts of reinforcing filler prepared in Example 2, 9 parts of modified polyurethane elastomer prepared in Example 2, 1 part of KH-570, 3 parts of molybdenum disulfide, and 0.3 parts of lubricant;
[0060] Step S1, weighing raw materials by weight, putting polyethylene, low-density polyethylene, medium-density polyethylene, the reinforcing filler prepared in Example 2, the modified polyurethane elastomer prepared in Example 2, KH-570, molybdenum disulfide and stearic acid into an internal mixer, and mixing at 170° C. for 15 minutes to obtain a rubber mixture;
[0061] Step S2, pouring the mixed rubber into a mold and subjecting it to hot pressing and cold pressing to obtain a scratch-resistant PE composite board.
[0062] Example 6: A method for preparing a scratch-resistant PE composite board comprises the following steps:
[0063] 85 parts of polyethylene (molecular weight 4 million), 7 parts of low-density polyethylene, 5 parts of medium-density polyethylene, 8 parts of reinforcing filler prepared in Example 3, 12 parts of modified polyurethane elastomer prepared in Example 3, 2 parts of KH-570, 4 parts of molybdenum disulfide, and 0.4 parts of lubricant;
[0064] Step S1, weighing raw materials by weight, putting polyethylene, low-density polyethylene, medium-density polyethylene, the reinforcing filler prepared in Example 3, the modified polyurethane elastomer prepared in Example 3, KH-570, molybdenum disulfide and stearic acid into an internal mixer, and mixing at 180° C. for 20 minutes to obtain a rubber mixture;
[0065] Step S2, pouring the mixed rubber into a mold and subjecting it to hot pressing and cold pressing to obtain a scratch-resistant PE composite board.
[0066] Comparative Example 1: This comparative example is a PE composite board, which differs from Example 6 in that calcium carbonate is used instead of the reinforcing filler prepared in Example 3, and the rest are the same.
[0067] Comparative Example 2: This comparative example is a PE composite board. The difference from Example 6 is that polyolefin elastomer is used instead of the modified polyurethane elastomer prepared in Example 3, and the rest are the same.
[0068] The PE composite plates prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:
[0069] Impact strength test: The samples were tested for impact strength according to GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics - Part 1: Non-instrumented impact test";
[0070] Scratch resistance test: According to the general standard PV3952, the test conditions are: load 6N, scratch cone tip diameter 1mm, scratch moving speed 500mm / min, use a colorimeter to test the absolute value of the color difference before the sample is scratched L1, and the absolute value of the color difference after the sample is scratched L2. Subtract the two values before and after (L1-L2), and take the absolute value to get the color difference ΔL * , color difference ΔL * The smaller the value, the better the scratch resistance of the material.
[0071] Hardness test: Place the sample horizontally, with the pressure needle of the hardness tester facing downward and 90° vertical to the sample. Keep the pressure needle in contact with the sample for 1 second and start reading. Select 5 different positions for measurement, ensuring that the distance between the measurement points is 6mm. Take the average of the measured values to obtain the surface Shore hardness value of the sample.
[0072] Anti-ultraviolet aging performance test: According to the national standard GB / T 16422.3-2014, the sample is placed in a UV accelerated aging test chamber. The temperature of the UV aging chamber is 50±3℃. The exposure cycle is drying for 5 hours and spraying for 1 hour. Samples are taken after 48 hours. The impact strength of the sample after aging is tested and the impact strength change rate is calculated.
[0073] The test results are shown in Table 1:
[0074] Table 1: Performance test results
[0075]
[0076] It can be seen from Table 1 that after the impact strength, scratch resistance, hardness, and UV aging resistance tests, the impact strength of the PE composite board prepared by the present invention is (35.2-40.1) KJ / m 2 Within the range, the color difference is (0.92-0.96)ΔL * The hardness is in the range of (43.9-46.6)D, and the impact strength change rate is in the range of (-23.9)%-(-25.3)%, indicating that the PE composite board has excellent toughness, scratch resistance, hardness and anti-ultraviolet aging performance, and can be widely used in chemical, food, medical, construction and other fields.
[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A scratch-resistant PE composite board, characterized in that: The invention comprises the following raw materials in parts by weight: 65-85 parts of polyethylene, 3-7 parts of low-density polyethylene, 2-5 parts of medium-density polyethylene, 3-8 parts of reinforcing filler, 5-12 parts of modified polyurethane elastomer, 0.5-2 parts of silane coupling agent, 2-4 parts of molybdenum disulfide, and 0.2-0.4 parts of lubricant; The molecular weight of the polyethylene is between 2.8 million and 4 million; The reinforcing filler is prepared by the following steps: Step A1, mixing and stirring the nanocellulose in ethanol, and then transferring the mixture to a planetary ball mill for ball milling at a ball-to-material ratio of 10:1 for 3-6 hours to obtain pre-treated nanocellulose; Step A2, adding pretreated nanocellulose, 4-dimethylaminopyridine, β-alanine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and fluorenylmethoxycarbonyl chloride to N,N-dimethylformamide in sequence and mixing evenly, stirring at room temperature for 10-15 hours, centrifuging, washing, collecting the preproduct, and then dispersing the preproduct in 20% piperidine N,N-dimethylformamide solution, stirring for 20-40 minutes, centrifuging, washing, and freeze-drying to obtain modified nanocellulose; Step A3, mix p-phenylenediamine and triethylamine in N,N-dimethylformamide and stir evenly, then add cyanuric chloride and modified nanocellulose and ultrasonicate for 20-40 minutes, then transfer to an autoclave, react at 120°C for 8-12 hours, centrifuge, wash and dry to obtain a reinforced filler.
2. The scratch-resistant PE composite board according to claim 1, characterized in that: In step A1, the mass ratio of nanocellulose to ethanol is 3-10:0.5-3.
3. The scratch-resistant PE composite board according to claim 1, characterized in that: In step A2, the dosage ratio of pre-treated nanocellulose, 4-dimethylaminopyridine, β-alanine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, fluorenylmethoxycarbonyl chloride, N,N-dimethylformamide and piperidine N,N-dimethylformamide solution is 1-3 g: 0.08-0.24 g: 1.5-4.5 g: 1.25-3.75 g: 0.75-2.25 g: 50-100 mL: 20-40 mL.
4. The scratch-resistant PE composite board according to claim 1, characterized in that: In step A3, the dosage ratio of p-phenylenediamine, triethylamine, N,N-dimethylformamide, cyanuric chloride and modified nanocellulose is 5.4-16.2 g: 7-14 mL: 200 mL: 4.6-13.8 g: 1-3 g.
5. The scratch-resistant PE composite board according to claim 1, characterized in that: The silane coupling agent is KH-570, and the lubricant is stearic acid.
6. The scratch-resistant PE composite board according to claim 1, characterized in that: The modified polyurethane elastomer is prepared by the following steps: Step B1, 2,2-dihydroxymethylpropionic acid, epichlorohydrin and tetrabutylammonium bromide are mixed uniformly in N,N-dimethylformamide, and then nitrogen is introduced for 10 minutes, reacted under nitrogen and 80-90° C. for 3-5 hours, rotary evaporated, and then 25wt% sodium hydroxide solution is slowly added dropwise, and reacted at 60-70° C. for 2-3 hours, washed and dried to obtain a terminal epoxy product; Step B2, 2-hydroxy-4-methoxybenzophenone, the terminal epoxy product and chloroform are mixed and stirred evenly, an ion exchange resin is added, and then transferred to a water bath, reacted at 50-60° C. for 2-3 hours, filtered, and rotary evaporated to obtain a terminal hydroxyl product; Step B3, dehydrate polyethylene glycol under vacuum at 130°C for 1-2h, introduce argon, then cool to 75-95°C, add isophorone diisocyanate and dibutyltin dilaurate, react for 2.5-4.5h, then add toluene and the terminal hydroxyl product, stir and react for 2-3h, to obtain a modified polyurethane elastomer.
7. The scratch-resistant PE composite board according to claim 6, characterized in that: In step B1, the usage ratio of 2,2-dihydroxymethylpropionic acid, epichlorohydrin, tetrabutylammonium bromide, N,N-dimethylformamide and sodium hydroxide solution is 0.1-0.2 mol: 0.1-0.2 mol: 0.005-0.01 mol: 100 mL: 30 mL.
8. The scratch-resistant PE composite board according to claim 6, characterized in that: In step B2, the usage ratio of 2-hydroxy-4-methoxybenzophenone, terminal epoxy product, chloroform and ion exchange resin is 1.14-3.42 g: 0.88-2.64 g: 5-15 mL: 0.5-1.5 g.
9. The scratch-resistant PE composite board according to claim 6, characterized in that: In step B3, the usage ratio of polyethylene glycol, isophorone diisocyanate, dibutyltin dilaurate, toluene and terminal hydroxyl product is 0.1 mol: 0.13-0.25 mol: 0.001-0.003 mol: 50 mL: 4-8 g.
10. A method for preparing the scratch-resistant PE composite board according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, putting polyethylene, low-density polyethylene, medium-density polyethylene, reinforcing filler, modified polyurethane elastomer, silane coupling agent, molybdenum disulfide and lubricant into an internal mixer, and mixing at 160-180° C. for 10-20 minutes to obtain a rubber mixture; Step S2, pouring the mixed rubber into a mold and subjecting it to hot pressing and cold pressing to obtain a scratch-resistant PE composite board.
Citation Information
Patent Citations
Polyethylene wood plastic composite board modified through melt grafting of styrene and acrylic acid and preparation method thereof
CN107602975A
High-hardness scratch-resistant material and preparation method thereof
CN108070157A
Cited By
High-toughness modified PE material
CN121450001A